Weeds as important vegetables for farmers - Cruz García, Gisella S.; Price, LL (Polish Botanical Society, 2012)
The objective of this study was to investigate the multiple uses and cognitive importance of edible weeds in Northeast Thailand. Research methods included focus group discussions and freelistings. A total of 43 weeds consumed as vegetable were reported, including economic, naturalized, agricultural and environmental weeds. The weedy vegetables varied considerably on edible parts, presenting both reproductive (flowers, fruits and seeds) and vegetative organs (shoots, leaves, flower stalks, stems or the whole aerial part). The results of this study show that weedy vegetables are an important resource for rice farmers in this region, not only as a food but also because of the multiple additional uses they have, especially as medicine. The fact that the highest Cognitive Salience Index (CSI) scores of all wild vegetables freelisted corresponded to weeds, reinforces the assertion that weeds are culturally cognitively important for local farmers as a vegetable source. This is a key finding, given that these species are targets of common pesticides used in this region.